EVALUATION OF THE FACTORS AFFECTING THE DEVELOPMENT OF HUMAN RESOURCES IN STATE ENTERPRISES USING A MIXED METHOD (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Due to the increasing competition and instability in the business environment, proper management of human resources and employee growth have become crucial issues for organizations in achieving competitive advantage. This study aimed to analyze the factors influencing Human Resource Development (HRD) in State-Owned Enterprises (SOEs). This research is applied in terms of purpose and mixed (qualitative-quantitative) in terms of research design. Content analysis and descriptive research methods were used in the qualitative-quantitative part of the study. Data were collected through semi-structured interviews and questionnaires in the qualitative and quantitative parts, respectively. The research population includes specialists in the field of human resources, managers, and specialists in human resource planning and SOE management. A total of 25 people were selected as the target audience. In the qualitative part, data analysis was carried out using open, axial, and selective coding to classify the identified factors into four categories: organizational, occupational, behavioral, and empowerment factors. Additionally, screening was conducted using the Fuzzy Delphi method, and the relationships between the identified factors and sub-factors were determined using the Fuzzy DEMATEL method. During the study, it was concluded that empowerment factors are the most important determinants of HRD, which can be improved by considering relevant influencing factors and prioritizing organizational factors. On the other hand, the results of factor weighting based on the Fuzzy Analytic Network Process (FANP) showed that among the identified factors and sub-factors, knowledge management within the empowerment factors had the greatest impact on HRD.
Keywords: Human Resource Development (HRD), Qualitative-quantitative analysis, Fuzzy Delphi method, Fuzzy DEMATEL method, Fuzzy Analytic Network Process (FANP).